Redirection of Epithelial Immune Responses by Short-Chain Fatty Acids through Inhibition of Histone Deacetylases - Lin, May Young; de Zoete, Marcel R.; van Putten, Jos P. M.; Strijbis, Karin (Frontiers in Immunology, 2015)
Short-Chain Fatty Acids (SCFAs) are products of microbial fermentation that are important for intestinal epithelial health. Here we describe that SCFAs have rapid and reversible effects on Toll-like receptor (TLR) responses in epithelial cells. Incubation of HEK293 or HeLa epithelial cells with the SCFAs butyrate or propionate at physiological concentrations enhanced NF-κB activation induced by TLR5, TLR2/1, TLR4 and TLR9 agonists. NF-κB activation in response to TNFα was also increased by SCFAs. Comparative transcript analysis of HT-29 colon epithelial cells revealed that SCFAs enhanced TLR5-induced transcription of TNFα but dampened or even abolished the TLR5-mediated induction of IL-8 and monocyte chemotactic protein 1 (MCP-1). SCFAs are known inhibitors of histone deacetylases (HDACs). Butyrate or propionate caused a rapid increase in histone acetylation in epithelial cells, similar to the small molecule HDAC inhibitor Trichostatin A (TSA). TSA also mimicked the effects of SCFAs on TLR-NF-κB responses. This study shows that bacterial SCFAs rapidly alter the epigenetic state of host cells resulting in redirection of the innate immune response and selective reprogramming of cytokine/chemokine expression.